Green Financing as a Tool for the Implementation of Infrastructure Projects (Based on the Materials of the Transport Complex) - Elena MIDLER; Aleksey BELOSHITSKIY (Communications of International Proceedings, 2021)
The role of green bonds as a tool for attracting additional funds for the implementation of infrastructure projects is examined in the article based on the example of transport (railway) complexes: electrification of existing lines, modernization of rolling stock, implementation of other complex projects. A comparative analysis of the practice of using this financing mechanism in relation to the developed and developing railway markets of France, Germany, China and Russia is carried out, the role of green bonds in their financing is determined, the main principles of use in the infrastructure sphere are highlighted. Special attention is focused on the goals of green financing and the assessment of the volume of attracted funds for the green transformation of infrastructure facilities. The conclusion is made that there is no direct relationship between the volume of the issue of green bonds and their share in the total volume of investments in the development of the railway industry. The small share of green bonds in the structure of investments in the development of this industry indicates that the market is immature, and there is a great potential for growth.
Keywords: Green Finance; Green Bonds; Infrastructure Project; Railway Complex; Emerging Markets